FINANCIAL FEASIBILITY OF HOUSING INVESTMENT TYPE 36 IN THE CITY OF PALANGKA RAYA - Carles Willianson; Revianti Coenraad (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
The test results are the basis for analyzing whether housing construction type 36 was feasible. Analysis was carried out by the buyer's interest and determination. Likert’s scale analysis of financial feasibility is already done by using the criteria of Coast Benefit Ratio (BCR), Internal Rate of Return (IRR) and Break Event Point (BEP). Results of the research showed that buyers of Civil Servants very interested to have 36 types of homes in the city of Palangkaraya thus research was proceeding to the stage of financial analysts. The economic analysis of alternative cash flow techniques 1 (8 units), IRR = 28%> 11% (MARR), BCR = 1.05> 1, and BEP = 5. Cash flow alternative 1 (16 units) was IRR = 41,5 %> 11% (MARR), BCR = 1.08> 1, and BEP = 9 unit. Alternative cash flow 1 (24 units) was the value of IRR = 47.9%> 11% (MARR), BCR = 1.10> 1, and BEP = 7 units. Alternative cash flow 1 (32 units) was the value of IRR = 50.0%> 11% (MARR), BCR = 1.11> 1, and BEP = 7 units. Then the alternative cash flow 1 for feasible overall is based on the financial aspects. Cash flow analysis of alternative 2, and 3 have the same alternative, for the sale of 8 units acquired IRR = 12.3%> 11% (MARR), the value of BCR = 1.01>, and BEP = 8 units. Sales of 16 units acquired IRR = 14.9%> 11% (MARR), the value of BCR = 1.03> 1, and BEP = 16. For the sale of 24 units acquired IRR = 14.9%> 11% (MARR), the value of BCR = 1.03> 1, and BEP = 24 units, and for the sale of 32 units acquired IRR = 15.2%> 11% (MARR), the value of BCR = 1.03> 1, and BEP = 32 units. It is that the overall cash flow analysis of alternatives 2 and 3 were a feasible alternative based on the financial aspects. The economic analysis of alternative cash flow techniques 4 (8 units), IRR = 9.8% <11% (MARR), BCR = 0.99 < 1, which concluded that the alternative cash flow 4 (8 units) was not feasible based on financial aspects. Alternative cash flow 4 (16 units) is for value of IRR = 11.4%> 11% (MARR), BCR = 1.00> 1, and BEP = 16 units. Alternative cash flow 4 (24 units) is for the value of IRR = 11.7%> 11% (MARR), BCR = 1.01> 1, and BEP = 24 units. Alternative cash flow 4 (32 units) is for the value of IRR = 12.0%> 11% (MARR), BCR = 1.01> 1, and BEP = 32 units. So the alternative cash flow 4 with sales of 16 units, 24 units and 32 units for overall are feasible based on the financial aspects.